Studies of Sociology Conspiracy in Indonesian Politics Novel - Andharu, Devito; Supratno, Haris; Darni (Open Access Indonesia Journal of Social Sciences, 2022)
This study aims to find a conspiracy in Indonesian politics novels. This study uses a sociology conspiracy study to reveal the concepts of conspiracy in the novel. The research approach used is qualitative. Data collection techniques using library techniques. The data analysis technique used hermeneutic and heuristic methods. And the data validity technique uses time triangulation. The results show that conspiracy in Indonesian politics novels is related to conflicts creation, scenarios-paranoid creation, and the manipulation of events.